Building Long-Term Customer Relationships in Market Segments - Ardian Reeisafitra; Revina Adiningtyas; Dian Putri Wahyuningsih; Dava Arsila Pradana; Imeliya Briyan Fatona (Universitas Muhammadiyah Surakarta, 2026)
This article explores long-term customer relationships as a strategic imperative in segmented markets. The study focuses on the differences in consumer behavior between B2B and B2C contexts and how relationship-building strategies must adapt accordingly. Employing a qualitative approach through literature review and case analysis, the article synthesizes practical insights into CRM, personalization, and technology integration. Findings indicate that loyalty is influenced by emotional value in B2C and operational consistency in B2B, with CRM systems serving as the backbone for both. The study offers recommendations for implementing customer retention strategies across diverse segments.